The Role of Virtual Laboratories in Developing Students' Science Process Skills: A Systematic Literature Review - Yasfi Ismayani; Nilawati Nilawati; St. Hajar; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2023)
Science Process Skills (SPS) are a crucial foundation in science education, yet the limitations of physical laboratory facilities often hinder their development. This study aims to comprehensively examine the role of virtual laboratories as an innovative solution to enhance students' SPS. The method employed is a Systematic Literature Review (SLR) guided by PICO (Population, Intervention, Comparison, Outcome) criteria, analyzing literature published between 2016 and 2023. Data collection was conducted through reputable databases such as Scopus, Web of Science, Science Direct, and Google Scholar using the Publish or Perish application. The analysis results indicate that virtual laboratories play a vital role in enhancing SPS through interactive simulation features that enable the visualization of abstract concepts and flexible, safe experimentation. Despite its effectiveness, implementation faces challenges regarding the validity of simulation realism, interface design, and teacher pedagogical readiness. The study concludes that virtual laboratories are an effective catalyst for bridging theory and practice; however, they are most optimal when used as a complement to, rather than a total replacement for, physical laboratories.